«Водевиль в сумасшедшем доме»: «Линия Брунгильды» М. А. Алданова [“Vaudeville in a Madhouse”: “Liniia Brungil’dy” by Mark Aldanov] - Nikolayev, Dmitri (Slavica Revalensia, 2015)
If one were to single out the most characteristic feature of the Russian theatre in exile, it would be the severe scarcity of everything: theater troupes were small, productions were executed on a very meager budget, etc. Dmitri Nikolayev’s article discusses the way that Mark Aldanov adapted his style to meet this challenge, which resulted in the creation of “Liniia Brungil’dy” (1937), a play in the genre of vaudeville.